Demographic distribution and injury patterns of ankle physeal fractures in children: a retrospective cohort study - Silvia Valisena; Giacomo De Marco; Oscar Vazquez; Anne Tabard-Fougère; Nastassia Guanziroli-Pralong; Christina Steiger-Tuc; Romain Olivier Dayer; Dimitri Ceroni (Swiss Medical Weekly)
INTRODUCTION: Ankle physeal fractures are a significant concern in paediatric populations due to their potential to cause growth disturbances, including premature physeal closure. The present study aimed to describe the epidemiology and injury patterns of ankle physeal fractures in children treated at a single university hospital centre in Switzerland over a 19-year period.